Cone Beam Computerized Tomography Dacryocystography (CBCT DCG) for the Evaluation of Lacrimal Drainage System Dysfunction. Issue 6 (November 2020) - Karlin, Justin N.; Mustak, Hamzah; Gupta, Adit; Ramos, Regina; Rootman, Daniel B.
Abstract : Purpose: Lacrimal outflow imaging has been limited in clinical practice due to a combination of modality limitations and efficacy of clinical testing. Cone beam computed tomography dacryocystography (CBCT DCG) has certain advantages over other modalities that may enhance clinical utility. This study was intended to understand the relationships between symptoms, syringing and CBCT DCG in a population of patients presenting with tearing. Methods: Cross-sectional cohort study of adult patients undergoing both CBCT DCG and clinical probing and irrigation. Concordance analysis between symptoms, clinical examination, and CBCT DCG was performed at baseline and postoperatively in patients who were treated with dacryocystorhinostomy. Results: CBCT DCG findings correlate fairly well with probing/irrigation (Cohen kappa = 0.376). Excluding cases of canalicular obstruction identified by either method, the correlation between CBCT DCG and probing/irrigation was moderately improved (Cohen kappa = 0.488). There was no statistically significant difference in correlation with patient symptoms between CBCT DCG and probing/irrigation ( p = 0.877). Fifteen patients (17 lacrimal systems) patients underwent endoscopic dacryocystorhinostomy (DCR) surgery. Ten demonstrated absence of symptoms 90 days postoperatively, 3 endorsed continued tearing and 2 were lost to follow up. All 3 who demonstrated continued tearing, demonstrated canalicular obstruction on CBCT DCG which was not initially detected on probing/irrigation. Conclusions: CBCT DCG correlates moderately well with probing and irrigation, as well as patient symptoms. This technology may assist in identification of functional/anatomic canalicular obstruction. Abstract : With respect to identifying lacrimal system obstruction, cone-beam CT dacryocystography complements clinical evaluation of the lacrimal system using traditional probing and irrigation.